Follicular Proinflammatory Cytokines and Chemokines as Markers of IVF Success. (5th October 2011) - Sarapik, Aili; Velthut, Agne; Haller-Kikkatalo, Kadri; Faure, Gilbert C.; Béné, Marie-Christine; de Carvalho Bittencourt, Marcelo; Massin, Frédéric; Uibo, Raivo; Salumets, Andres
Abstract : Cytokines are key modulators of the immune system and also contribute to regulation of the ovarian cycle. In this study, Bender MedSystems FlowCytomix technology was used to analyze follicular cytokines (proinflammatory: IL-1 β, IL-6, IL-18, IFN- γ, IFN- α, TNF- α, IL-12, and IL-23;, and anti-inflammatory: G-CSF), chemokines (MIP-1 α, MIP-1 β, MCP-1, RANTES, and IL-8), and other biomarkers (sAPO-1/Fas, CD44(v6)) in 153 women undergoing in vitro fertilization (IVF). Cytokine origin was studied by mRNA analysis of granulosa cells. Higher follicular MIP-1 α and CD44(v6) were found to correlate with polycystic ovary syndrome, IL-23, INF- γ, and TNF- α with endometriosis, higher CD44(v6) but lower IL- β and INF- α correlated with tubal factor infertility, and lower levels of IL-18 and CD44(v6) characterized unexplained infertility. IL-12 positively correlated with oocyte fertilization and embryo development, while increased IL-18, IL-8, and MIP-1 β were associated with successful IVF-induced pregnancy.